Methods of conflict resolution of organizational and technical systems in the oil and gas industry - D. A. Pervukhin; H. Davardoost; D. D. Kotov (Современная наука и инновации)
Conflicts accompany projects in the oil and gas industry throughout all stages of their life cycle. Some conflicts contribute to achieving the goals of the project and improve its overall effectiveness; some may become an obstacle to its implementation. This can lead to delays, non-fulfillment of tasks and disruption of project deadlines. The present study is aimed at studying one of the stages of development of the South Pars gas field located in Asaluyeh, Iran. The results of the study focus on key issues related to the complexity of the project and conflicts that need to be resolved during its implementation. The main purpose of this study is to reveal the relationship between the project conflict and its complexity, which are revealed in the relationship between contractors and the company. In this paper, the organizational and technical system representing the South Pars gas field located in Asaluyeh, Iran, is chosen as the object of research. The data obtained from twelve experienced project specialists of various levels with work experience from 20 to 25 years were used as sources of information. The data obtained were processed using the Leximancer program and, based on the results of the study, conclusions and directions for conflict resolution were formulated. The results obtained indicate that the three main factors of conflict in the implementation of a project in the oil and gas industry, which lead to its complexity, are sanctions, time and cost of the project. In addition, the following also have a significant impact on the conflict: the scope of activity and intra-organizational communications.